2017
DOI: 10.1101/131946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional diversity among sensory neurons from efficient coding principles

Abstract: In many sensory systems the neural signal is coded by multiple parallel pathways, suggesting an evolutionary fitness benefit of general nature. A common pathway splitting is that into ON and OFF cells, responding to stimulus increments and decrements, respectively. According to efficient coding theory, sensory neurons have evolved to an optimal configuration for maximizing information transfer given the structure of natural stimuli and circuit constraints. Using the efficient coding framework, we describe two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 81 publications
4
21
1
Order By: Relevance
“…This is expected based on their classification (Supplementary Figs. 1B-D) and previous results 17,18,34,35 . In contrast, On-and Off-type neurons responded with similar increases in firing rate ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…This is expected based on their classification (Supplementary Figs. 1B-D) and previous results 17,18,34,35 . In contrast, On-and Off-type neurons responded with similar increases in firing rate ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Overall, the magnitude and source of noise can have a large effect on a circuit's ability to encode stimulus information (37,38,57,58). As a preliminary check, we confirmed that one of these known effects carries over to our convergent/divergent circuit.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, if a population is optimal in the sense described here, it would be possible to predict the natural distribution of the stimuli being encoded from the Fisher information measured from the population responses. Such an inverse efficient coding scheme is similar to a method proposed in [ 39 ], which derives the stimulus distribution from the distribution of firing thresholds in an optimal population of spiking neurons.…”
Section: Resultsmentioning
confidence: 99%